The synthesis of silica-based aerogel from gold mine waste for thermal insulation - Mermer, Nevin Karamahmut; Yilmaz, Muge Sari; Ozdemir, Ozgul Dere; Piskin, Mehmet Burcin (SPRINGER, 2017)
Energy consumption and increase in the greenhouse gases are very critical problem for all countries. In order to solve this problem, researches are focused on new thermal insulation materials that are the essential part of the energy-efficient buildings. Aerogels are called 'the best thermal insulating materials' due to their extremely low thermal conductivity. In this study, silica-based hydrophobic aerogel was synthesized by sol-gel method via ambient pressure drying. The silica source was obtained from the gold mine waste by alkali fusion method instead of using pure and expensive silica sources such as tetraethyl orthosilicate. The synthesized aerogels were used in the production of insulating plaster with different mass percentages (1, 5, 10, and 20%) and characterized by XRD, FT-IR, contact angle measurement, TG/DTA and N-2 adsorption/desorption analysis. In addition, the thermal conductivity of the aerogel-based plaster was determined by using TCi thermal conductivity analysis. The results show that addition of aerogel to plaster was decreased the thermal conductivity and when the mass percentage was 20% the thermal conductivity decreases of 63% as compared to the natural plaster without aerogel.
Keywords: Aerogel; Waste; Insulating plaster; Thermal conductivity; Hydrophobicity; AMBIENT-PRESSURE; CHERENKOV COUNTER; CARBON AEROGEL; FLY-ASH; REMOVAL; FILMS; Thermodynamics; Chemistry